2015
DOI: 10.1126/scisignal.aaa6922
|View full text |Cite
|
Sign up to set email alerts
|

HER2-mTOR signaling–driven breast cancer cells require ER-associated degradation to survive

Abstract: Targeting non-oncogenic vulnerabilities may provide additional therapeutic approaches in tumors that are resistant to oncogene-targeted therapy. Using a computational pathway-based approach, we interrogated clinical breast cancer genomic data sets for candidate non-oncogenic vulnerabilities in breast cancers that have genomic amplification of ERBB2, which encodes human epidermal growth factor 2 (HER2). HER2-positive (HER2(+)) breast cancers showed increased expression of genes encoding proteins in the endoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 59 publications
3
31
1
Order By: Relevance
“…The research efforts in cancer genomics have mainly www.impactjournals.com/oncotarget focused on the driver genes, and less attention has been given to the onco-passengers that have undergone similar CNVs as the driver genes. Previously, we showed that the pathway expression landscape of breast cancers with ERBB2 amplifications is largely driven by gene CNVs [16]. In this study, we confirm this finding at a broader scale, and show that onco-passenger gene expression has a significant contribution to the tumor transcriptomes.…”
Section: Discussionsupporting
confidence: 87%
“…The research efforts in cancer genomics have mainly www.impactjournals.com/oncotarget focused on the driver genes, and less attention has been given to the onco-passengers that have undergone similar CNVs as the driver genes. Previously, we showed that the pathway expression landscape of breast cancers with ERBB2 amplifications is largely driven by gene CNVs [16]. In this study, we confirm this finding at a broader scale, and show that onco-passenger gene expression has a significant contribution to the tumor transcriptomes.…”
Section: Discussionsupporting
confidence: 87%
“…Since disulfide bond formation occurs in the Endoplasmic Reticulum (ER), and HER2+ breast cancers are particularly sensitive to DDAs [33] and ER stress/ERAD [25], we examined whether DDAs (such as RBF3) activate the Unfolded Protein Response (UPR). In the DDA-sensitive MDA-MB-468, BT474, and SKBR3 lines, DDAs activated ER stress as indicated by GRP78 upregulation (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of HER2+ breast cancer cells to ERAD inhibition depends on continued protein synthesis [25]. The protein synthesis inhibitors cycloheximide (CHX) and puromycin function by interfering with the translocation step in protein synthesis and by inducing premature chain termination during translation, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence in favor of this comes from a study showing that tumor lines positive for the oncogene HER2 upregulate the ERAD machinery [72]. Crucially, cells unresponsive to HER2-targeting drugs are sensitive to ERAD inhibition, displaying the ERAD 'addiction' alluded to above.…”
Section: Physiolgoical and Pathological Roles Of Mammalian Derlinsmentioning
confidence: 99%